2019
DOI: 10.1096/fj.201900236r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoregulation of p38 activity enhances endoplasmic reticulum stress‐mediated inflammation by arterial endothelium

Abstract: Endothelial up‐regulation of VCAM‐1 at susceptible sites in arteries modulates the recruitment efficiency of inflammatory monocytes that initiates atherosclerotic lesion formation. We reported that hydrodynamic shear stress (SS) mechanoregulates inflammation in human aortic endothelial cells through endoplasmic reticulum (ER) stress via activation of the transcription factor x‐box binding protein 1 (XBP1). Here, a microfluidic flow channel that produces a linear gradient of SS along a continuous monolayer of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Bailey et al found that SS mechanoregulates the inflammatory response of human aortic ECs through activating the transcription factor XBP1 via ER stress, during which a temporal, SS-regulated rise in p38 phosphorylation activates XBP1 nuclear translocation and promotes the highest expression of vascular cell adhesion protein 1 (VCAM-1). In summary, a possible mechanism is that SS sensitizes the ECs to cytokine-induced ER stress, thereby modulating inflammation that promotes atherosclerosis [ 30 , 31 ]. In addition, SS induces human aortic EC apoptosis, the mechanism of which involves ER stress mediated by the interleukin-1 receptor-associated kinase 2 (IRAK2)/CHOP signaling pathway [ 32 ].…”
Section: Proatherogenic Effects Of Er Stress In Different Cell Typmentioning
confidence: 99%
“…Bailey et al found that SS mechanoregulates the inflammatory response of human aortic ECs through activating the transcription factor XBP1 via ER stress, during which a temporal, SS-regulated rise in p38 phosphorylation activates XBP1 nuclear translocation and promotes the highest expression of vascular cell adhesion protein 1 (VCAM-1). In summary, a possible mechanism is that SS sensitizes the ECs to cytokine-induced ER stress, thereby modulating inflammation that promotes atherosclerosis [ 30 , 31 ]. In addition, SS induces human aortic EC apoptosis, the mechanism of which involves ER stress mediated by the interleukin-1 receptor-associated kinase 2 (IRAK2)/CHOP signaling pathway [ 32 ].…”
Section: Proatherogenic Effects Of Er Stress In Different Cell Typmentioning
confidence: 99%
“…The mitogen-activated protein kinase (MAPK)/p38 signaling pathway is well known to exert a crucial role in balancing cell survival and cell death [9][10][11]. Inhibition of the MAPK/p38 signaling pathway is known to suppress cell apoptosis and the expression of pro-inflammatory cytokines in related cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…p38 has attracted increased attention in inflammation, and p38 kinase plays a central role in inflammatory responses ( 29 31 ). Moreover, inhibition of p38 activation has been demonstrated to suppress LPS-induced inflammation ( 29 , 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the Nrf2/HO-1 signaling pathway also inhibits the activation of NLRP3 inflammasome, thus reducing IL-1β expression and exerting anti-inflammatory and cytoprotective effects ( 27 , 28 ). p38 kinase, which is a member of the mitogen-activated protein kinase (MAPK) family, plays a central role in inflammatory responses in a variety of disease models, such as Parkinson's disease, cancer and inflammatory disease ( 29 31 ), and has been the subject of basic research and drug discovery ( 32 ). Furthermore, inhibition of p38 activation has been revealed to suppress LPS-induced inflammation in different situations, such as in LPS-induced inflammation in IPEC-J2 cells, bronchial epithelial cells, macrophages and rats ( 29 , 33 35 ).…”
Section: Introductionmentioning
confidence: 99%